Massive hiatal hernia involving prolapse of the entire stomach and pancreas resulting in pancreatitis and bile duct dilatation: a case report - Hidenori Tomida; Masahiro Hayashi; Shinichi Hashimoto (Surgical Case Reports, 2020)
Abstract Background Hiatal hernia is defined by the permanent or intermittent prolapse of any abdominal structure into the chest through the diaphragmatic esophageal hiatus. Prolapse of the stomach, intestine, transverse colon, and spleen is relatively common, but herniation of the pancreas is a rare condition. We describe a case of acute pancreatitis and bile duct dilatation secondary to a massive hiatal hernia of pancreatic body and tail. Case presentation An 86-year-old woman with hiatal hernia who complained of epigastric pain and vomiting was admitted to our hospital. Blood tests revealed a hyperamylasemia and abnormal liver function test. Computed tomography revealed prolapse of the massive hiatal hernia, containing the stomach and pancreatic body and tail, with peripancreatic fluid in the posterior mediastinal space as a sequel to pancreatitis. In addition, intrahepatic and extrahepatic bile ducts were seen to be dilated and deformed. After conservative treatment for pancreatitis, an elective operation was performed. There was a strong adhesion between the hernial sac and the right diaphragmatic crus. After the stomach and pancreas were pulled into the abdominal cavity, the hiatal orifice was closed by silk thread sutures (primary repair), and the mesh was fixed in front of the hernial orifice. Toupet fundoplication and intraoperative endoscopy were performed. The patient had an uneventful postoperative course post-procedure. Conclusion A rare massive hiatal hernia, involving the stomach and pancreatic body and tail, can cause acute pancreatitis with bile duct dilatation. The etiology can be flexure of the main pancreatic and extrahepatic bile ducts. Symptomatic herniation is best treated with surgery. Elective surgery is thought to be safer than emergent surgery in patients with serious complications.